1998
DOI: 10.1212/wnl.51.3.803
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic anatomy of tremor in Parkinson's disease

Abstract: The findings suggest that PD patients with tremor are characterized by distinct increases in the functional activity of thalamo-motor cortical projections. Modulation of this functional anatomic pathway is likely to be the mechanism for successful interventions for the relief of parkinsonian tremor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
72
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(78 citation statements)
references
References 16 publications
6
72
0
Order By: Relevance
“…In agreement with the general clinical impression that STN is superior to GPi as a treatment target, 49,50 the magnitude of PDRP suppression was higher for interventions involving the former structure. The finding that PDRP expression is not altered by Vim DBS for severe PD tremor is also consistent with prior studies suggesting different mechanisms underlying the akinetic-rigid and tremulous manifestation of the disease 51,52 in PD patients undergoing Vim DBS for intractable PD tremor. 53 Significant reductions in PDRP expression have also been observed following pharmacological intervention.…”
Section: Metabolic Brain Network In Parkinson S Diseasesupporting
confidence: 90%
See 1 more Smart Citation
“…In agreement with the general clinical impression that STN is superior to GPi as a treatment target, 49,50 the magnitude of PDRP suppression was higher for interventions involving the former structure. The finding that PDRP expression is not altered by Vim DBS for severe PD tremor is also consistent with prior studies suggesting different mechanisms underlying the akinetic-rigid and tremulous manifestation of the disease 51,52 in PD patients undergoing Vim DBS for intractable PD tremor. 53 Significant reductions in PDRP expression have also been observed following pharmacological intervention.…”
Section: Metabolic Brain Network In Parkinson S Diseasesupporting
confidence: 90%
“…51 Additionally, we used PCA to characterize patterns associated with visuospatial and memory function in PD, 43,48 as well as affective symptoms. We found 48 that mnemonic functioning correlated with a specific metabolic pattern involving parietal decrements, covarying with increases in temporal cortex, pons, and cerebellum.…”
Section: Metabolic Brain Network In Parkinson S Diseasementioning
confidence: 99%
“…This prospective study using high-resolution MRI VBM to compare brain morphology of the different motor phenotypes of PD demonstrates for the first time a structural abnormality in the cerebellum in PD with rest tremor and highlights the postulated cerebellar involvement in the pathogenesis of rest tremor [16,42,61]. Rest tremor has been shown to correlate with increased metabolic [3,15,22] and oscillatory activity [64] in the cerebellum, thalamus and motor cortex. Those structures are connected by somatotopically organized cerebello-thalamo-cortical projections, and the posterior quadrangular lobule (lobule VI) of the cerebellar cortex has been shown to be linked with the hand area of the motor cortex [43].…”
Section: Discussionmentioning
confidence: 78%
“…These findings are highly consistent with previous studies that have shown a strong link between the “hyperfunctional” status of the thalamus and resting tremor (Bergman & Deuschl, 2002; Fukuda et al., 2004; Mehanna et al., 2014; Rehncrona et al., 2003; Wintermark et al., 2014). For example, patients with parkinsonian resting tremor show enhanced thalamic metabolism (Antonini et al., 1998; Kassubek et al., 2001), increased thalamic gray matter volumes (Kassubek, Juengling, Hellwig, Spreer, & Lucking, 2002), and higher thalamic activity (Helmich, Bloem, & Toni, 2011) compared with controls. Here, our results demonstrate that the previously reported “hyperfunctional” status of the thalamus is also present at the level of the whole‐brain network, which leads to increased thalamic centrality.…”
Section: Discussionmentioning
confidence: 99%